Chromosome fragile sites in Arabidopsis harbor matrix attachment regions that may be associated with ancestral chromosome rearrangement events. - Joelle S dela Paz; Patti E Stronghill; Scott J Douglas; Sandy Saravia; Clare A Hasenkampf; C Daniel Riggs (PLoS Genetics)
Mutations in the BREVIPEDICELLUS (BP) gene of Arabidopsis thaliana condition a pleiotropic phenotype featuring defects in internode elongation, the homeotic conversion of internode to node tissue, and downward pointing flowers and pedicels. We have characterized five mutant alleles of BP, generated by EMS, fast neutrons, x-rays, and aberrant T-DNA insertion events. Curiously, all of these mutagens resulted in large deletions that range from 140 kbp to over 900 kbp just south of the centromere of chromosome 4. The breakpoints of these mutants were identified by employing inverse PCR and DNA sequencing. The south breakpoints of all alleles cluster in BAC T12G13, while the north breakpoint locations are scattered. With the exception of a microhomology at the bp-5 breakpoint, there is no homology in the junction regions, suggesting that double-stranded breaks are repaired via non-homologous end joining. Southwestern blotting demonstrated the presence of nuclear matrix binding sites in the south breakpoint cluster (SBC), which is A/T rich and possesses a variety of repeat sequences. In situ hybridization on pachytene chromosome spreads complemented the molecular analyses and revealed heretofore unrecognized structural variation between the Columbia and Landsberg erecta genomes. Data mining was employed to localize other large deletions around the HY4 locus to the SBC region and to show that chromatin modifications in the region shift from a heterochromatic to euchromatic profile. Comparisons between the BP/HY4 regions of A. lyrata and A. thaliana revealed that several chromosome rearrangement events have occurred during the evolution of these two genomes. Collectively, the features of the region are strikingly similar to the features of characterized metazoan chromosome fragile sites, some of which are associated with karyotype evolution.